The Roles Of Woman In Nggorea Village In Order To Increase The Economic Social Of Family By Local Weaving Cloth Heritage - Hasti Sulaiman; Anita Anita (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2020)
The aims of this research is to describe the roles of woman in Nggorea village in order to increase the economic social of family by local weaving cloth heritage. This research is a descriptive qualitative. Data collected by direct observation, documentation, and interview. In this research shows that beside as the housewife, the woman at Nggorea village roles to increase the economic in their family by using the local weaving cloth, which is the culture heritage of the ancestor. Generally, the activity of weaving by woman in Nggorea village is just to spend their time after finishing the homework and to continue the culture heritage. The product of woven cloth can be used as the daily clothing and as used at the culture ceremony. Meanwhile, to fulfill their daily life needs are getting by gardening and fishing. However, the product of woven cloth is known by many people and the function of the woven cloth is varied such as to make a coat, bag, skirt, blanket, and so on. The quality of woven cloth give an effect to its price, so it can influenced the economic social of Nggorea society. There are some kinds of social economic increasing at Nggorea village, such as fulfill the life needs and to get the higher education so that it can influence to the better social life. Automatically it influenced to the social status of society.